Dampak pandemi COVID-19 terhadap harga minyak dan pangan dunia: Analisis VECM - Reninta Dewi Nugraheni, M.Sc.; Ika Inayah (Jurnal Ekonomi dan Pembangunan, 2022)
The study investigates the impacts of the COVID-19 pandemic on global oil price, global food price index, meat, and sugar commodity price index using vector error correction (VECM) model covering the sample period of 1st April 2020 to 31st August 2021. Data were collected mainly from WHO, FAO, and Macro Trend Websites. The result from VECM model indicates a strong cointegration relationship among the variables. In the short run, global oil price, meat price index, and sugar price index are negatively and significantly related to the COVID-19 pandemic. In the long run, the prices of these variables do not follow to the others, but there is negative reaction of global oil prices to meat and sugar price index. The COVID-19 pandemic increased the meat and sugar price index, but not significantly at the 5% level.